Clinical Trial in a Dish: Personalized Stem Cell–Derived Cardiomyocyte Assay Compared With Clinical Trial Results for Two QT‐Prolonging Drugs - Blinova, Ksenia; Schocken, Derek; Patel, Dakshesh; Daluwatte, Chathuri; Vicente, Jose; Wu, Joseph C.; Strauss, David G. (Clinical and translational science, 2019)
Induced pluripotent stem cells (iPSCs) have shown promise in investigating donor‐specific phenotypes and pathologies. The iPSC‐derived cardiomyocytes (iPSC‐CMs) could potentially be utilized in personalized cardiotoxicity studies, assessing individual proarrhythmic risk. However, it is unclear how closely iPSC‐CMs derived from healthy subjects can recapitulate a range of responses to drugs. It is well known that QT‐prolonging drugs induce subject‐specific clinical response and that all healthy subjects do not necessarily develop arrhythmias or exhibit similar amounts of QT prolongation. We previously reported this variability in a study of four human ether‐a‐go‐go‐related gene (hERG) potassium channel–blocking drugs in which each subject underwent intensive pharmacokinetic and pharmacodynamic sampling such that subjects had 15 time‐matched plasma drug concentration and electrocardiogram measurements throughout 24 hours after dosing in a phase I clinical research unit. In this study, iPSC‐CMs were generated from those subjects. Their drug‐concentration‐dependent QT prolongation response from the clinic was compared with in vitro drug‐concentration‐dependent action potential duration (APD) prolongation response to the same two hERG‐blocking drugs, dofetilide and moxifloxacin. Comparative results showed no significant correlation between the subject‐specific APD response slopes and clinical QT response slopes to either moxifloxacin (P = 0.75) or dofetilide (P = 0.69). Similarly, no significant correlation was found between baseline QT and baseline APD measurements (P = 0.93). This result advances our current understanding of subject‐specific iPSC‐CMs and facilitates discussion into factors obscuring correlation and considerations for future studies of subject‐specific phenotypes in iPSC‐CMs.